22. New frontiers in neurophysiological instrumental diagnostics in the neonatal intensive care unit: "Smart-EEG". Issue 12 (December 2017) - Capuano, I.; Gabbanini, S.; Bastianelli, M.; Cossu, C.; Roma, I.; Lori, S.
Abstract : The neurophysiological instrumental diagnostics is gaining increasingly an undisputed value, revealing an indispensable practice for both diagnostic and prognostic purposes. Many novelties in medicine have introduced an innovative model of Electronic Health, called E-Health. The purpose of this study is to verify that a new modular device, the BluNet®, is a device able to maximize patient comfort and to operate in a way effective but minimally invasive. The study was conducted on a sample of 10 neonates (5F), with gestational ages between the 27 + 6 and 41 weeks, and the recordings were done simultaneously with two devices: NeMus® (gold standard) and BluNet. We made a visual comparison with the reading software, we extracted and compared the frequency of polygraphic channels (ECG and abdominal breathing) and we made two Bland-Altman-Plots. We also conducted a spectral analysis of the traces. The signals' studies showed that there aren't substantial differences between the signals acquired through the two different methods. BluNet, thanks to its innovative features, is a valid tool for electroencephalographic evaluation and the prospects for future use are manifold: screening for early differential diagnosis, initial evaluation for possible hospitalization, ability to get tests at home.